2008
DOI: 10.1093/treephys/28.11.1619
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition is not the main factor influencing variability in carbon isotope composition of tree rings

Abstract: From June to December, we determined the effects of variations in biochemical composition on delta(13)C of tree rings of 2-year-old oaks (Quercus petraea (Matt.) Liebl.) growing under semi-natural conditions, and the dependence of these effects of water stress during the growth season. Percent abundance, carbon concentration and delta(13)C were measured in holocellulose, lignin, extractive-free wood, starch and a water-soluble fraction. Relative concentrations of lignin and holocellulose in the extractive-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
2
15
0
2
Order By: Relevance
“…The isotopic composition of whole-wood was compared with that of cellulose in larger samples to establish the relationship between the two. They typically show similar patterns in d 13 C with somewhat higher values in cellulose (Helle and Schleser 2004;Loader et al 2003, Verheyden et al 2005Harlow et al 2006;Eglin et al 2008). This was confirmed for the series of Carapa and Goupia that were used for this comparison (Fig.…”
Section: Resultssupporting
confidence: 74%
“…The isotopic composition of whole-wood was compared with that of cellulose in larger samples to establish the relationship between the two. They typically show similar patterns in d 13 C with somewhat higher values in cellulose (Helle and Schleser 2004;Loader et al 2003, Verheyden et al 2005Harlow et al 2006;Eglin et al 2008). This was confirmed for the series of Carapa and Goupia that were used for this comparison (Fig.…”
Section: Resultssupporting
confidence: 74%
“…In contrast, d 13 C values measured with the IRMS system were obtained from extracted cellulose. Several studies have demonstrated an offset between d 13 C of whole wood and cellulose, which is constant and independent of season (Livingston and Spittlehouse 1996;Borella et al 1998;Leuenberger et al 1998;Eglin et al 2008).…”
Section: Carbon Isotopesmentioning
confidence: 99%
“…Verificou-se empobrecimento em 13 C na lignina nas espécies que compõem o CLU de 3,57 ‰ e nas que colonizam a FES de 2,30 ‰ (Quadro 5), em relação ao conjunto do tecido vegetal, e esse foi acima do preconizado por Eglin et al (2008), que foi de 1-2 ‰ de δ 13 C, com relação ao conjunto tecido vegetal.…”
Section: Composição Isotópica Da Lignina E Da Celulose Da Vegetaçãounclassified
“…De maneira geral, a celulose é enriquecida em 1-2 ‰ de δ 13 C, em relação ao tecido vegetal (Leavitt & Long, 1986). Durante a lignificação, ocorre fracionamento isotópico por causa da deposição lenta da lignina em relação à produção de celulose, ocasionando nessa um enriquecimento em 13 C. A molécula de lignina possui aproximadamente 50 % a mais de C que a de celulose e a maior parte desse carbono é 12 C. O aumento de 10 % no teor de lignina na planta promove enriquecimento de 0,25 a 0,47 ‰ nos valores de δ 13 C da fração celulose (Eglin et al, 2008).…”
Section: Composição Isotópica Da Lignina E Da Celulose Da Vegetaçãounclassified